CUIDADOS AO RECÉM-NASCIDO PREMATURO EM USO DE SONDA OROGÁSTRICA: CONHECIMENTO DA EQUIPE DE ENFERMAGEM - Larissa Bento De Araújo Mendonça; Marta Muniz de Menezes; Karla Maria Carneiro Rolim; Francisca Elisângela Teixeira Lima (Universidade Federal do Ceará, 2010)
The objectives of the study were to describe the knowledge of the nursing team on the care to newborns using orogastric probe (OGP) and identify the necessary care in its passage and maintenance. It was a descriptive, qualitative study, carried through in a neonatal unit of a public maternity of Fortaleza-CE, Brazil. The collection of data came about by means of a half-structuralized interview with eleven nurse aides on questions referring to the procedure of passage and maintenance of the OGP in premature babies. As a result of the nursing team knowledge it was cited the correct passage technique, as well as setting, maintenance of the OGP; the care with the diet and the necessity to promote the interaction between mother and son for the establishment of the affective bond. It was so concluded that the nursing team showed appropriate knowledge to pass, fix and maintain the OGP in the newborn. We also emphasize the concern that the team has with the mother-child binomial, especially on the use of OGP by the newborn.